2013
DOI: 10.1021/bi400489b
|View full text |Cite
|
Sign up to set email alerts
|

Conformational Differences between the Methoxy Groups of QA and QB Site Ubisemiquinones in Bacterial Reaction Centers: A Key Role for Methoxy Group Orientation in Modulating Ubiquinone Redox Potential

Abstract: Ubiquinone is an almost universal, membrane-associated redox mediator. Its ability to accept either one or two electrons allows it to function in critical roles in biological electron transport. The redox properties of ubiquinone in vivo are determined by its environment in the binding sites of proteins and by the dihedral angle of each methoxy group relative to the ring plane. This is an attribute unique to ubiquinone among natural quinones and could account for its widespread function with many different red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
50
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 17 publications
(56 citation statements)
references
References 48 publications
6
50
0
Order By: Relevance
“…31 The unpaired spin density giving rise to the 13 C isotropic hyperfine coupling for the methoxy group carbon atom arises from a combination of spin polarization and hyperconjugation. When the methoxy group is held in the ring plane, hyperconjugation is expected to be zero and small negative hyperfine couplings are expected for in-plane or near to in-plane orientations, due to spin polarization by the methoxy oxygen spin density.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…31 The unpaired spin density giving rise to the 13 C isotropic hyperfine coupling for the methoxy group carbon atom arises from a combination of spin polarization and hyperconjugation. When the methoxy group is held in the ring plane, hyperconjugation is expected to be zero and small negative hyperfine couplings are expected for in-plane or near to in-plane orientations, due to spin polarization by the methoxy oxygen spin density.…”
Section: Discussionmentioning
confidence: 99%
“…5,31 However, as noted above, these data are currently not available for the SQ i in the Q i site, because approaches for selective isotopic labeling of proteins and cofactors have not been developed in Rb. sphaeroides .…”
mentioning
confidence: 99%
“…The influence of the methoxy group orientation was not investigated. In the light of these results and also recent studies reported on conformational differences between the methoxy groups of Q A and Q B site ubisemiquinones in RCs of Rhodobacter sphaeroides [4][5][6] a detailed theoretical DFT investigation of the 2-and 3-methoxy rotational potential energy encompassing various ubisemiquinone model H-bonded structures was initiated with a view to elucidating the influence of both methoxy group conformation and hydrogen bond donation on the ubiquinone electron affinity. Firstly the influence of the isoprenoid side chain of the ubisemiquinone (USQ-n, see Scheme 1) on the electron affinity of the quinone is investigated.…”
Section: Introductionmentioning
confidence: 95%
“…Previous DFT/EPR experiments have concluded that different orientations of the 2-methoxy group (but not the 3-methoxy group; Fig. 2) in Q A and Q B are responsible for establishing the functional quinone redox potential difference (810). …”
Section: Introductionmentioning
confidence: 93%